2002
DOI: 10.1159/000064356
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Microwave Tissue Coagulator: Is It Beneficial to Partial Nephrectomy?

Abstract: Background/Aim: The indications of partial nephrectomy have expanded after the introduction of new techniques for preventing excessive blood loss and avoiding deterioration of the renal function after clamping the renal pedicle. We present our clinical experience of partial nephrectomy for renal tumors using a microwave tissue coagulator. Patients and Methods: Between April 1996 and January 2000, 34 patients underwent open partial nephrectomies in the Kobe City General Hospital. The microwave tissue coagulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Especially during wedge resection, safe resection has been achieved using microwave tissue coagulation without vascular control, which differs from other new techniques [12]. However, in larger resections, combination with other techniques might be necessary to decrease blood loss and the rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Especially during wedge resection, safe resection has been achieved using microwave tissue coagulation without vascular control, which differs from other new techniques [12]. However, in larger resections, combination with other techniques might be necessary to decrease blood loss and the rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…In urology, microwave energy has been successful in prostate surgery for both benign enlargement and malignant disease. A microwave coagulator has been utilized clinically by Kagebayashi [13,14,15,16,17,48]. For LPN, Yoshimura et al [18] reported its use in six patients with small exophytic renal masses (11-25 mm in diameter) without renal pedicle clamping at a setting of 2450 MHz.…”
Section: Microwave Coagulationmentioning
confidence: 99%
“…[11][12][13] The MTC causes thermal coagulation of tissues, using microwave energy (2459 MHz). This energy is transmitted from the generator through a coaxial cable to the probe, which consists of a handpiece and a needle-like electrode.…”
Section: Introductionmentioning
confidence: 99%